Chrysin Sensitizes Human Lung Cancer Cells to Tumour Necrosis Factor Related Apoptosis-Inducing Ligand (TRAIL) Mediated Apoptosis - Mehdi, Syed Hassan; Zafaryab, Md; Nafees, Sana; Khan, Asad; Ahmad, Irfan; Hafeez, Zubair Bin; Rizvi, Moshahid Alam (Asian Pacific Journal of Cancer Biology, 2019)
Background: Lung cancer is the primary cause of cancer deaths worldwide. Thus, the requisite for more coherent methods to lung cancer therapy is needed. Purpose: Chrysin (5, 7-dihydroxyflavone) is a naturally occurring flavonoid having a wide range of pharmacological properties and is commonly found in fruits, vegetables, honey and propolis. In our study, we have hypothesized that chrysin would have anticancer activity on L132 lung cancer cell line. Methods: The cytotoxic effects were assessed by MTT and NRU assay. DAPI was used to evaluate the cell death. The pro- or anti-apoptotic proteins were detected by Western Blot assay, and, besides, mRNA expression was analysed with RT-PCR. In silico study of chrysin was performed to identify suitable inhibitors against the protein function. Results: Results indicated that chrysin enhanced the inhibitory effects of TRAIL (Tumour Necrosis Factor Related Apoptosis-Inducing Ligand) in comparison to TNF-α (tumour necrosis factor) on cell viability in L132 lung cancer cells and altered nuclear morphology of cells was observed in DAPI (4’,6-diamidino-2-phenylindole) staining after 48 hrs treatment. Treatment with chrysin enhances TRAIL-induced apoptosis by increasing the expression of apoptosis-related proteins including caspase-3, 8, 9 and Bax, whereas the expression of Bcl-2 was decreased. Chrysin was docked with caspase-3, 8, 9, Bax, and Bcl-2 proteins to identify suitable inhibitors against the protein function. Conclusion: We concluded that chrysin sensitizes lung cancer cells to TRAIL-induced apoptosis and may be considered for future studies as a promising therapeutic candidate for human lung cancer.